2019
DOI: 10.3390/ijms20081892
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Responses of Jurkat Lymphocytes to Simulated Microgravity Conditions

Abstract: The presence of microgravity conditions deeply affects the human body functions at the systemic, organ and cellular levels. This study aimed to investigate the effects induced by simulated-microgravity on non-stimulated Jurkat lymphocytes, an immune cell phenotype considered as a biosensor of the body responses, in order to depict at the cellular level the effects of such a peculiar condition. Jurkat cells were grown at 1 g or on random positioning machine simulating microgravity. On these cells we performed: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…The s-microgravity was established using a desktop RPM connected to a control console through standard electrical cables (Dutch Space, Leiden, The Netherlands). The main characteristics of this apparatus were previously described [45,54,55] and the use parameters reported in the manufacturer's manual. Briefly, the RPM is a 3D clinostat whose running exerts continuous changes in orientation of the biological sample in order to minimize the gravitational force vector.…”
Section: Equipment and Cell Exposure Parametersmentioning
confidence: 99%
“…The s-microgravity was established using a desktop RPM connected to a control console through standard electrical cables (Dutch Space, Leiden, The Netherlands). The main characteristics of this apparatus were previously described [45,54,55] and the use parameters reported in the manufacturer's manual. Briefly, the RPM is a 3D clinostat whose running exerts continuous changes in orientation of the biological sample in order to minimize the gravitational force vector.…”
Section: Equipment and Cell Exposure Parametersmentioning
confidence: 99%
“…Though our results showed a slight decrease of the expression of the ICAM-3 surface marker on the RPM group in Jurkat/A4 cells, in comparison to the control, we conclude that ICAM-3 also may be an important adhesion molecule involved in the induction of leukocyte apoptosis and the functions of cell growth behavior in microgravity conditions. As demonstrated recently, the transitory effects induced by stimulated microgravity on cell shape and proliferation are accompanied by metabolic changes that are, above all, related to mitochondrial activity [16]. The modification of external forces caused by stimulated microgravity conditions induced transient modifications in cell shape and intracellular density in Jurkat cells, accompanied by transient changes in the expression levels of some cytoskeletal proteins such as actin, tubulin, and vimentin, which are not only structural proteins but also the main functional milestones in cytoskeleton dynamics [42,43].…”
Section: Discussionmentioning
confidence: 74%
“…Most studies indicated that cells of the immune system are highly sensitive to altered gravity [16][17][18]. Jurkat cells are stable cellular models easily able to be managed, and lymphocytes can be considered as biosensors of the whole-body response and of adaptation to environmental conditions [16,28]. As reviewed by Morabito et al, shear stress during rotation, and the use of a depleted medium that cannot be renewed, impacts the outcomes of exposure lasting longer than 96 h [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations